2016
DOI: 10.1039/c5ra24209f
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorhydrazide inhibitors: toxicological profile and antimicrobial evaluation assay, molecular modeling and QSAR study

Abstract: A series of 23 novel phosphorhydrazide derivatives were synthesized and characterized by spectral techniques, and their anti-ChE, antibacterial and insecticide activities were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…QSAR study of toxicity of phoshorhydrazide (PHA) derivates revealed that the NH-P(X) moiety has a much higher inhibitory activity than the NH-C(X) moiety. The presence of the electron acceptor substituent around the P=X group increases the inhibitory potential of the PHA derivatives [14]. Obtained results are in accordance with previous findings of QSTR modeling of toxicity of organic molecules to Daphnia magna [4].…”
Section: Resultssupporting
confidence: 81%
“…QSAR study of toxicity of phoshorhydrazide (PHA) derivates revealed that the NH-P(X) moiety has a much higher inhibitory activity than the NH-C(X) moiety. The presence of the electron acceptor substituent around the P=X group increases the inhibitory potential of the PHA derivatives [14]. Obtained results are in accordance with previous findings of QSTR modeling of toxicity of organic molecules to Daphnia magna [4].…”
Section: Resultssupporting
confidence: 81%
“…A number of phosphoramide compounds and their organotin(IV) complexes have been structurally studied [ [6] , [7] , [8] ], where some of them have significant medicine applications such as antiviral, antitumor and anticancer activities [ [9] , [10] , [11] , [12] ]. Antibacterial and antimicrobial properties also have been found for some of phosphoramidate derivatives [ [13] , [14] , [15] , [16] ]. Moreover, some of these compounds are found to be the significant promising candidates to inhibit coronavirus [ [17] , [18] , [19] ]: some of the current not-optimal anti-coronavirus drugs, Remdesivir and Sofosbuvir, belong to the phosphoramides family [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even if both P-N bond lengths are shortened when compared to the sum of the covalent radii calculated by Pyykkö (2015) [single: AEr cov (P-N) = 1.82 Å , double: AEr cov (P-N) = 1.62 Å ], the P V -N distance [P1-N1 = 1.6561 (11) Å ] is noticeably shorter than the P III -N distance [P2-N2 = 1.7049 (11) Å ]. The more pronounced reduction of P V -N bond lengths of phosphoryl hydrazine entities [range from 1.6587 (15) to 1.6989 (10) Å ; Gholivand et al, 2012Gholivand et al, , 2016Hö hne et al, 2018] in comparison to phosphane hydrazine P III -N distances [range from 1.692 (2) to 1.728 (2) Å ; Kriel et al, 2010;Aluri et al, 2010;Sushev et al, 2008] is documented. The N-N distance within the hydrazine unit amounts to 1.4256 (16) Å and conforms to the sum of the covalent radii calculated by Pyykkö (2015)…”
Section: Structure Descriptionmentioning
confidence: 97%